Multimedia Teaching Effectiveness in Natural Science Teaching - Maričić, Olja; Ivkov-Džigurski, Anđelija; Stojšić, Ivan; Cvjetićanin, Stanko; Ivanović Bibić, Ljubica (Geographica Pannonica, 2019)
The aim of this research is to examine the difference in the contribution of the created multimedia models and the traditional teaching to the quality and durability of the students’ knowledge of geographical content at all cognitive levels in the fourth grade of the primary school (10-11 years). This research included a sample of 142 students, divided into two groups: E (experimental) and C (control). The students in the C group were taught in the traditional way and the students of the E group taught using the created multimedia models. The quality of students’ knowledge was examined by a post-test, while the durability of knowledge was examined by re-test. Variations in knowledge on post-test and re-test in both groups were observed at cognitive levels. At a higher cognitive level (analysis), students were better at re- testing than at a post-test. In the application of geographic contents in the fourth grade, multimedia teaching (MT) should be given priority over traditional teaching (TT).